Hydrobiogeochemistry of redox-sensitive components: A special issue in tribute to Zhaoli Shen. (November 2022) - Wang, Yanxin; Guo, Huaming; Polya, David A.; Liu, Zaihua
Abstract: Professor Zhaoli Shen, Emeritus Professor in the China University of Geosciences and Foreign Academician of the Russian Academy of Engineering, was one of the greatest pioneers in hydrogeochemical studies in China and beyond. He left us forever on April 4, 2020, at the age of 88. In this Zhaoli Shen Tribute Issue, twenty-three submissions were accepted which focus on hydrobiogeochemistry of redox-sensitive components in groundwater systems and can be classified into five themes: (1) Interaction among water, gas, rock, and microbes in aquifer systems; (2) Natural organic matter and its role in redox-sensitive component mobility; (3) Isotopic signatures of redox-sensitive component sources and biogeochemical processes; (4) Roles of hydrogeochemical and hydrogeological processes in the distribution of redox-sensitive components; and (5) Removal of redox-sensitive contaminants. This special issue thus highlights the importance of hydrobiogeochemical processes in controlling the cycling of redox-sensitive elements in aquifer systems.